Pressure and perfectionism: a phenomenological study on parents’ and teachers’ perceptions of the challenges faced by gifted and talented students in self-contained classes - Noor, Bushra (Frontiers in Education, 2023)
This qualitative study sought to examine the challenges of pressure and perfectionism among gifted and talented students in self-contained class settings at the primary level, based on the experiences of their teachers and parents. To obtain comprehensive details and complete descriptions from the participants, a phenomenological design was used to collect data from 13 participants, including 10 parents and 3 teachers of gifted and talented students through semi-structured interviews. The major findings indicate that while self-contained classes help to raise the academic potential of gifted and talented students, teachers and parents were concerned about challenges related to the pressure of a competitive environment along with the pressure of high expectations and perfectionism in these selective class settings that may hinder the student’s academic development and negatively affect their social–emotional wellbeing. Using full-time ability grouping practices in self-contained settings for gifted learners was quite challenging and could hamper their talent development. This study recommends that pressure and perfectionism can be overcome if educators use flexible grouping practices, motivational strategies and encourage feedback in such settings. Consequently, educators and policy makers in gifted education should plan and implement educational provisions that help to meet the academic as well as social emotional needs of highly intellectual learners.